Three-dimensional structure of the regular surface glycoprotein layer of Halobacterium volcanii from the Dead Sea - Kessel, Martin (1988)
A three-dimensional reconstruction from electron micrographs of negatively stained cell envelopes of Halobacterium volcanii has revealed the structure of the surface glycoprotein to a resolution of 2 nm. The glycoprotein is arranged on a p6 lattice with a lattice constant of 16.8 nm. It forms 4.5 nm high, dome-shaped, morphological complexes with a narrow pore at the apex opening into a `funnel' towards the cell membrane. The polarity of the structure was derived from freeze-etching experiments and `edge' views. Six radial protrusions emanate from each morphological complex and join around the 3-fold axis to provide lateral connectivity. Using the primary structure of the surface glycoprotein of the closely related species Halobacterium halobium (Lechner and Sumper, 1987) and the cell envelope profile from a previous X-ray analysis of the same species (Blaurock et al., 1976) we have integrated our reconstruction into a model of halobacterial cell envelope.